Pengaruh Metode Role Playing terhadap Hasil Belajar Kognitif Ditinjau dari Aktivitas Belajar Siswa - Asrorul Azizi; Irwansah Irwansah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2020)
The method of role playing in learning is a teaching and learning process in which students themselves are mentally active, building their knowledge, which is based on the cognitive structure they have. The teacher has a more role as a facilitator and mediator of learning. This study aims to determine the effect of role playing methods on cognitive learning outcomes in terms of student learning activities. The research method used is a quasi-experimental method. The research design used a